JAG1, Regulated by microRNA-424-3p, Involved in Tumorigenesis and Epithelial–Mesenchymal Transition of High Proliferative Potential-Pituitary Adenomas - Chen, Yiyuan; Li, Bin; Feng, Jie; Fang, Qiuyue; Cheng, Jianhua; Xie, Weiyan; Li, Chuzhong; Cheng, Sen; Zhang, Yazhuo; Gao, Hua (Frontiers in Oncology, 2020)
Pituitary adenomas (PAs) are a neoplastic proliferation of anterior pituitary. Signature of Notch pathway relies upon the histopathological type of PAs. The details of Notch pathway that are involved in the migration and invasion of Pas are still unclear. This paper filters and testifies the relation between Notch signaling pathway and the migration/invasion in subtypes of PAs. The diversity of genes and pathways is investigated based on transcriptome data of 60 patients by KEGG pathway analysis and GSEA. A series of functional experiments demonstrate the role of candidate genes by overexpression and antibody blocking in GH3 cell line. Volcano map and GSEA results exhibit the differential and the priority of Jagged1 canonical Notch Ligand (JAG1) in the Notch pathway combined with clinical features. JAG1 is involved in epithelial–mesenchymal transition (EMT) in PAs by correlation analysis of RNA-seq data. Progression-free survival (PFS) of patients with high JAG1 was shorter than patients with low JAG1 according to follow-up data (P = 0.006). Furthermore, overexpression and antibody blocking experiments in GH3 cell line indicate that JAG1 could promote cell proliferation, migration, and G1/S transition. Double luciferase reporter assay gives manifests that JAG1 is the target gene of miR-424-3p, and mimics or inhibitor of miR-424-3p can regulate the level of JAG1 which, in turn, affects cell proliferation and the levels of MMP2 and VIM in GH3 cell line, respectively. Our study delves into the relation between the Notch signaling pathway and cell proliferation and EMT in PAs, providing a potential treatment through targeting JAG1.